Density Measurement of Molten Drop With Aerodynamic Levitation and Laser Heating - Gong, Yaopeng; Zhang, Li; Yuan, Yidan; Guo, Qiang; Ma, Weimin; Huang, Shanfang (Frontiers in Energy Research, 2022)
Thermophysical properties of molten core materials (corium) are necessary input parameters of models and computer codes which predict the severe accident progression in light water reactors. The corium contains the components of UO2, ZrO2, Zr and Fe. The measurement of molten corium properties is a very challenging task due to high melting points of corium which can reach 3000K. This paper presents a density measurement system for a molten drop based on techniques of aerodynamic levitation, laser heating and image processing. A sphere of alumina was firstly levitated by argon gas flow above a conical converging-diverging nozzle. The sphere was then heated up and melted into a liquid drop by a laser beam. The shape of the drop was recorded by a high-speed camera, and the density was calculated from image processing.